2014
DOI: 10.1021/nn5003024
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Recognition Enables Nanosubstrate-Mediated Delivery of Gene-Encapsulated Nanoparticles with High Efficiency

Abstract: Substrate-mediated gene delivery is a promising method due to its unique ability to preconcentrate exogenous genes onto designated substrates. However, many challenges remain to enable continuous and multiround delivery of the gene using the same substrates without depositing payloads and immobilizing cells in each round of delivery. Herein we introduce a gene delivery system, nanosubstrate-mediated delivery (NSMD) platform, based on two functional components with nanoscale features, including (1) DNA⊂SNPs, su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(55 citation statements)
references
References 59 publications
(124 reference statements)
0
55
0
Order By: Relevance
“…This mechanism, the so‐called the central dogma, derives its importance from the fact that it can be applied to metabolism‐mimicking synthetic cell designs in the same context. To date, however, the creation of synthetic cells has consisted of simply trapping exogenous genomes into polymer complexes and studying synthetic metabolism mimicry …”
Section: Methodsmentioning
confidence: 99%
“…This mechanism, the so‐called the central dogma, derives its importance from the fact that it can be applied to metabolism‐mimicking synthetic cell designs in the same context. To date, however, the creation of synthetic cells has consisted of simply trapping exogenous genomes into polymer complexes and studying synthetic metabolism mimicry …”
Section: Methodsmentioning
confidence: 99%
“…49 The combination of cyclodextrin-grafted branched PEI, adamantane-grafted polyamidoamine, adamantine-grafted poly(ethylene glycol, PEG), and Si NWs achieved efficient delivery of DNA supramolecular nanoparticles in mice. 49 …”
Section: In Vivo Applicationsmentioning
confidence: 99%
“…Since 2007, the majority of the research has been on in vitro applications of nanoneedles/nanowires. In early 2014, Tseng and co‐workers reported an in vivo study of substrate‐mediated gene delivery, as shown in Figure . In their delivery system, two nanoscale features were included: 1) DNA‐SNPs (supramolecular nanoparticles) as a vector for gene encapsulation, and 2) adamantane (Ad)‐grafted silicon nanowire substrates.…”
Section: Physical Approaches For Intracellular Deliverymentioning
confidence: 99%
“…The Ad/CD recognition system is also responsible for the supramolecular assembly of DNA‐SNPs from the three molecular building blocks (i.e., CD‐PEI, Ad‐PAMAM, and Ad‐PEG) and plasmid DNA. Reproduced with permission . Copyright 2014, American Chemical Society.…”
Section: Physical Approaches For Intracellular Deliverymentioning
confidence: 99%